Management of Guidance and Counseling Services in Improving Self-Efficacy and Student Learning Motivation in Schools During the Covid-19 Pandemic: Manajemen Layanan Bimbingan dan Konseling dalam Meningkatkan Self Efficasy dan Motivasi Belajar Siswa di Sekolah Pada Masa Pandemi Covid-19 - Nunung Faizah; Eni Fariyatul Fahyuni (Academia Open, 2022)
An educational institution is an institution that carries a person into an orderly and systematic flow of thought. In this sense, education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills that are treated by the people of the nation and state. Guidance and counseling management is a student service starting from the acceptance of new students, the development of student coaching both personal, social, learning and career services. Researchers used qualitative research with a phenomenological approach. The researcher attended the school through observation, conducting interviews and documentation in order to analyze the application of guidance and counseling service management to improve student self-efficacy and learning motivation at SMK Muhammadiyah 2 Taman during the covid 19 pandemic. The data obtained were then analyzed and concluded. The results showed that the implementation of guidance and counseling service management to improve student self-efficacy and learning motivation at SMK Muhammadiyah 2 Taman during the covid 19 pandemic was carried out through several stages, namely planning, organizing, implementing, monitoring, and evaluating. Then the results of the researchers are that with guidance and counseling services students experience an increase in self-efficacy and learning motivation after the service and guidance process is carried out.